2013
DOI: 10.1590/s1413-78522013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Resultados de revisão de artroplastia total do joelho com haste não cimentada "Press-fit"

Abstract: OBJECTIVE: To show our experience with press-fit cementless stem and metaphyseal fixation with cement in a selected series of patients who underwent revision total knee arthroplasty. METHODS: Thirty-four patients (35 knees) underwent revision total knee arthroplasty using the press-fit technique. Minimum follow-up was one year (mean 2.2 years) with a maximum length of three years. RESULTS: Of 34 patients, 20 were women and 14 were men. There was one death due to causes not related to arthroplasty and one patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Some studies reported good long‐term results of cemented stems with proposed advantages of excellent initial stability, less micro‐motion and increased flexibility of implant placement [15, 32]. Whiles others argued that a diaphyseal engaging cementless stem would avoid stress shielding around this area and facilitate probable component removal during rerevision [6, 12, 15, 23, 34, 48]. It revealed in the present study comparable mid‐ to long‐term clinical and radiographical outcomes of both fixation techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported good long‐term results of cemented stems with proposed advantages of excellent initial stability, less micro‐motion and increased flexibility of implant placement [15, 32]. Whiles others argued that a diaphyseal engaging cementless stem would avoid stress shielding around this area and facilitate probable component removal during rerevision [6, 12, 15, 23, 34, 48]. It revealed in the present study comparable mid‐ to long‐term clinical and radiographical outcomes of both fixation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Certain guidelines and proposal regarding meta‐analyses of observational studies were followed to suppress inherent bias in study designs [34, 47]. Studies without clarification of complications of special interventions were excluded during qualitative synthesis [13, 23, 25] (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%